Tradisi Ketek Cor Sebagai Media Komunikasi Mengharmoniskan Hubungan Dengan Ida Sang Hyang Widhi Wasa - Bagus Ade Tegar Prabawa; I Nyoman Surpa Adisastra; Edy Chandra (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Tradition Ketek Cor implies the meaning and symbols used in its implementation. In addition, Ketek Cor tradition can be a liaison for transcendent communication between the community and Ida Bhatara Dalem Tegal, this shows the occurrence of harmony between religious and social life in the Tegal Darmasaba Traditional Village community. Based on the above background, the purpose of this research is why the cast armpit tradition is still being implemented. In connection with this, there are several theories that are used as a guide in reviewing research problems, including: Structural Functional Theory, Communication Theory of symbolic Interactionalism perspective and System theory. The ketek cor tradition is still being carried out today, namely as a means for the people of Tegal to communicate the history of the ketek cor tradition. The implementation of the ketek cor tradition can also harmonize the relationship with Ida Sang Hyang Widhi Wasa of the Tegal community, namely the existence of the cast iron tradition is able to foster a sense of sradha and devotion to the Tegal community, as a form of gratitude, as a form of worship, as an expressive function of the community.